Unsaturation degree of dated palm kernel oil and its potential as precursor for epoxidation / Mohd Qamarul Akmal Mohd Zaki and Siti Khatijah Jamaludin - Mohd Zaki, Mohd Qamarul Akmal; Jamaludin, Siti Khatijah (2021)
Vegetable oils are triglycerides derived from plants and made up of chains of fatty acids that it can be saturated or unsaturated depending on the number of carbon-carbon double bonds. This research work was aimed to characterized the palm-based oil (fresh palm kernel oil (PKO), dated PKO, oleic acid, fresh palm olein and dated palm olein) on characterizations and to investigate feasibility of dated PKO as precursor for epoxidation and compare its performance with fresh PKO. The epoxidation reaction was completed with formic acid (HCOOH) as oxygen carrier and hydrogen peroxide (H2O2) as oxygen donor with 90 minutes of reaction time by using a mol ratio of PKO:HCOOH:H2O2 at 1:1:1. The optimum percentage of relative conversion oxirane (%RCO) for fresh PKO and dated PKO was 3.4% and 3.0% respectively was recorded at 50 minutes of reaction time. The ageing of the PKO does not effects the the time of PKO to epoxidized. The iodine value (IV) for fresh and dated PKO was 13.642 g I2/100g and 12.373 g I2/100g was recorded the lowest compared to other oils. Thus, the result of these studies indicate that the dated PKO may be a precursor for epoxidation process due to its performance. In order to further expand this study, it is suggested to investigate additional value-added capabilities after ring opening, as epoxides were very active compounds.